1/3(5y-2)+1/12(6y+13)

Simple and best practice solution for 1/3(5y-2)+1/12(6y+13) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1/3(5y-2)+1/12(6y+13) equation:


y in (-oo:+oo)

(1/3)*(5*y-2)+(1/12)*(6*y+13) = 0

1/3*(5*y-2)+1/12*(6*y+13) = 0

1/3*(5*y-2)+1/12*(6*y+13) = 0

13/6*y+5/12 = 0

13/6*y+5/12 = 0

13/6*y+5/12 = 0 // - 5/12

13/6*y = -5/12 // : 13/6

y = -5/12/13/6

y = -5/26

y = -5/26

See similar equations:

| -3-4n= | | -5n=80 | | W^2+5wj-24j^2=0 | | 4x-7-9x=28 | | 3x+10-7x=70 | | -2x+8y=-6 | | -5y-5[-6-2y]=0 | | y-5.5=0 | | -33.072-(-41.03)= | | -2[-7k+4]+9=-13 | | 2x-88-117= | | -4(2n+3)+7(n+2)=15 | | 8x^2-10x+1=0 | | 8x-11x+7=9-3x+2 | | 15-[4m-5]=32 | | 1/168=x/100 | | -27=-2v | | 13x+7[-3x-1]=-63 | | x/100-1/168 | | 1/2w+2 | | 5x-2x-9=-9+3x | | 60=168x | | 13x+7[-3-1]=-63 | | -3x-6y=-5 | | 9x-7+x=-3+2x-4 | | -70z-0.6=-80z+1.8 | | 1/2-88-117 | | 3x^4-5x^2+2x^3=0 | | 3x^4-5x^2-2x^3=0 | | -9[6+u]-2u=-10 | | 2x+6y=-8 | | x^2y^6/x^5y^6 |

Equations solver categories